Frequency, Regional Variation, and Predictors of Undetermined Cause of Death in Cardiometabolic Clinical Trials: A Pooled Analysis of 9259 Deaths in 9 Trials. Issue 7 (12th February 2019) - Fanaroff, Alexander C.; Clare, Robert; Pieper, Karen S.; Mahaffey, Kenneth W.; Melloni, Chiara; Green, Jennifer B.; Alexander, John H.; Jones, W. Schuyler; Harrison, Robert W.; Mehta, Rajendra H.; Povsic, Thomas J.; Moreira, Humberto G.; et al.
Abstract : Background: Modern cardiometabolic clinical trials often include cardiovascular death as a component of a composite primary outcome, requiring central adjudication by a clinical events committee to classify cause of death. However, sometimes the cause of death cannot be determined from available data. The US Food and Drug Administration has indicated that this circumstance should occur only rarely, but its prevalence has not been formally assessed. Methods: Data from 9 global clinical trials (2009–2017) with long-term follow-up and blinded, centrally adjudicated cause of death were used to calculate the proportion of deaths attributed to cardiovascular, noncardiovascular, or undetermined causes by therapeutic area (diabetes mellitus/pre–diabetes mellitus, stable atherosclerosis, atrial fibrillation, and acute coronary syndrome), region of patient enrollment, and year of trial manuscript publication. Patient- and trial-level variables associated with undetermined cause of death were identified using a logistic model. Results: Across 127 049 enrolled participants from 9 trials, there were 9259 centrally adjudicated deaths: 5012 (54.1%) attributable to cardiovascular causes, 2800 (30.2%) attributable to noncardiovascular causes, and 1447 (15.6%) attributable to undetermined causes. There was variability in the proportion of deaths ascribed to undetermined causes by trial therapeutic area, region of enrollment, and year of trial manuscript publication. On multivariable analysis, acute coronary syndrome or atrial fibrillation trial (versus atherosclerotic vascular disease or diabetes mellitus/pre–diabetes mellitus), longer time from enrollment to death, more recent trial manuscript publication year, enrollment in North America (versus Western Europe), female sex, and older age were associated with greater likelihood of death of undetermined cause. Conclusions: In 9 cardiometabolic clinical trials with long-term follow-up, approximately 16% of deaths had undetermined causes. This provides a baseline for quality assessment of clinical trials and informs operational efforts to potentially reduce the frequency of undetermined deaths in future clinical research. Abstract : Supplemental Digital Content is available in the text.